DENTAL ANXIETY AND BEHAVIORAL PROBLEMS: A STUDY OF PREVALENCE AND RELATED FACTORS AMONG A GROUP OF INDIAN CHILDREN AGED 6-12 - Periasamy, Yashila; Jeevanandan, Ganesh; Ganapathy , Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Children’s dental anxiety is a natural developing feeling which is expected when meeting unfamiliar faces.Strange sounds and tastes,having to lie down and even pain.Dental fear is a normal emotional reaction to one or more specific threatening stimuli in the dental situation whereas dental anxiety denotes a state of apprehension that something dreadful is going to happen in relation to dental treatmentThis cross-sectional investigation was approved and 100 children among 6-12 years old registered at the paediatric clinic of Saveetha Dental College and Hospitals,in 2019.Children who did not need to undergo dental procedure using the local anaesthesia and children with systemic disease, psychological disorder, and developmental problems were not included into this study.The parents from this study had diploma and higher educational level as well.Prior dental visit,at the waiting room,the parents were asked to answer a questionnaire.The questionnaire had two sections ; first section of the questionnaire gathered information about the parents’ background and the second section of the questionnaire had a Corah dental anxiety scale (CDAS).Descriptive statistics were produced and data analaysis was performed. A total number of 100 children, 60 boys and 40 girls were participated in this study. Most of the children were 6-7 years old (40.67%) . The mean scores of the child’s dental anxiety and cooperative behaviour during the local anesthesia injection were 20.81 and 3.04, respectively ..High prevalence of severe dental anxiety may be seen in early years of school. It seems that general factors such as family factors have less impact on behavior of school aged children in a dental visit.